Multifrequency-swept optical coherence microscopy for highspeed full-field tomographic vibrometry in biological tissues - Choi, Samuel (Biomed Opt Express, 2017)
Because conventional laser Doppler vibrometry or Doppler optical coherence tomography require mechanical scanning probes that cannot simultaneously measure the wide-range dynamics of bio-tissues, a multifrequency-swept optical coherence microscopy with wide-field heterodyne detection technique was developed. A 1024 × 1024 × 2000 voxel volume was acquired with an axial resolution of ~1.8 μm and an acquisition speed of 2 s. Vibration measurements at 10 kHz were performed over a wide field of view. Wide-field tomographic vibration measurements of a mouse tympanic membrane are demonstrated to illustrate the applicability of this method to live animals.